Absolute age determination in South-West Greenland. The Julianehaab Granite, the Ilímaussaq Batholith and the Kûngnât Syenite Complex - Moorbath, S.; Webster, R. K.; Morgan, J. W. (Meddelelser om Grønland, 1960)
Rubidium-strontium age measurements for the Julianehaab Granite and for the Ilímaussaq Batholith give values of 1590 ± 70 m.y. and 1086 ± 19 m.y. respectively (using a value of 5.0 x 1010y. for the half-life of rubidium). These represent the maximum and minimum values for the age of the Gardar Formation, which is thus Precambrian. The results furthermore show that the Ketilidian Basement rocks (pre Julianehaab Granite) of South-West Greenland are themselves Precambrian. A rubidium-strontium determination from the Kûngnât Syenite Complex also gives a Precambrian age (1240 ± 150) indicating possible contemporaneity with the Ilímaussaq Batholith. Two potassium-argon age measurements are reported and are found to be in broad agreement with the rubidium-strontium data.